Three-dimensional Atomic Configurations in a ZnFe2O4 Single Crystal by X-ray Fluorescence Holography - Hosokawa, Shinya; Hayashi, Koichi; Matsushita, Tomohiro; Happo, Naohisa (E-journal of surface science and nanotechnology, 2025)
Three dimensional atomic structures of a zinc ferrite Franklinite ZnFe2O4 crystal were investigated by X-ray fluorescence holography with an atom-resolved and element-selected functions at room temperature. The obtained holograms were analyzed using a sparse modeling approach of a L1-regression. From the present experiment and analysis, it was found that Zn atoms are located at tetrahedral A sites, which is in good agreement with the existing X-ray diffraction data. On the other hand, well-damped atomic images are observed around the central Fe atom. The present results are discussed by comparing with existing neutron diffraction and X-ray absorption fine structure experiments, where cation exchange occurs between Zn and Fe atoms for fine particles by about 10–15%, but the existence of cation exchanges is not clarified by considering the positional fluctuations of the Fe atoms at the B sites.